Review on Thermal Performance of Nanofluids With and Without Magnetic Fields in Heat Exchange Devices - Yang, Jiawang; Yang, Xian; Wang, Jin; Chin, Hon Huin; Sundén, Bengt (Frontiers in Energy Research, 2022)
Addition of nanoparticles into a working fluid may improve heat transfer performance of the base fluid in heat exchangers. In this work, preparation method and process of nanofluids are introduced, and thermal properties of nanofluids, such as thermal conductivity and viscosity, are discussed in detail. A comprehensive literature survey on applications and limitations of nanofluids has been compiled. This paper also aims to review the natural and forced convective heat transfer characteristics of nanofluids with and without magnetic fields. The discussion for the natural convective heat transfer of nanofluids focuses on the heat transfer performance of non-conventional enclosures and electric heaters. The effects on the heat transfer due to variations of heating walls are also investigated and summarized. Specific application of nanofluids in trapezoid ribs tube, double-tube heat exchangers and plate heat exchanges have been reviewed and presented in the discussion about forced convective heat transfer. The previous results show that the inlet temperature of nanofluids obviously affects the heat transfer characteristics of double-tube heat exchangers, whereas multi-walled carbon nanotube-water nanofluid shows significant advantages in plate heat exchangers. Finally, this paper studies the natural convective heat transfer of magnetic fluid in a square cavity and forced convection heat transfer in a straight tube and a corrugated structure under the action of magnetic fields. It is found that the heat transfer performance of Fe3O4-water nanofluid is enhanced when a magnetic field is applied to the corrugated plate heat exchangers, and the pressure drop can be reduced by around 10%. This review puts forward an effective solution to improvement of thermal performance in heat transfer equipment and provides the basis for applications of nanofluids in the heat transfer field.